Emergence and spread of novel H5N8, H5N5 and H5N1 clade 2.3.4.4 highly pathogenic avian influenza in 2020. Issue 1 (1st January 2021) - Lewis, Nicola S.; Banyard, Ashley C.; Whittard, Elliot; Karibayev, Talgat; Al Kafagi, Thamer; Chvala, Ilya; Byrne, Alex; Meruyert (Akberovna), Saduakassova; King, Jacqueline; Harder, Timm; Grund, Christian; Essen, Steve; et al.
ABSTRACT: Analyses of HPAI H5 viruses from poultry outbreaks across a wide Eurasian region since July 2020 including the Russian Federation, Republics of Iraq and Kazakhstan, and recent detections in migratory waterfowl in the Netherlands, revealed undetected maintenance of H5N8, likely in galliform poultry since 2017/18 and both H5N5 and H5N1. All viruses belong to A/H5 clade 2.3.4.4b with closely related HA genes. Heterogeneity in Eurasian H5Nx HPAI emerging variants threatens poultry production, food security and veterinary public health.